Inpatient Burden, Costs, and Characteristics of Peripheral Artery Disease in Slovenia - Tjaša Furlan; Borut Jug; Jerneja Farkaš-Lainščak; Dalibor Gavrić; Irena Ograjenšek; Petra Došenović Bonča (Slovenian Journal of Public Health, 2026)
Abstract Introduction We assessed inpatient burden, costs, demographics, comorbidity patterns, and outcomes of peripheral artery disease (PAD) in Slovenia. Methods We included patients hospitalised for PAD (primary diagnosis, International Classification of Diseases, 10th revision, code I70.2–I70.9) in Slovenia between January 1st, 2015, and December 31st, 2022. We estimated crude and age-standardised hospitalisation rates, hospitalisation reimbursement costs, patient characteristics (age and sex distribution, disease severity and prevalence of comorbidities), uptake of revascularisation, major amputations and in-hospital mortality. Results We included 15,978 patients (60% men, median age 72 years, 32% chronic limb-threatening ischaemia) with 27,139 hospital episodes, yielding a mean of ~3,400 hospitalisations per year (hospitalisation rate 161 per 100,000/year). Median direct cost (inflation-adjusted to 2025) per hospital episode was €3,177, yielding total costs of €10.8 million/year. The most common comorbidities were arterial hypertension (35%), dyslipidemia (21%) and diabetes mellitus (19%), with a significantly higher prevalence in patients with chronic limb-threatening ischaemia. During the observation period, revascularisation procedures increased from 77.5% to 80.2%, while major amputations decreased from 13.2% to 7.9%, and mortality decreased from 5.0% to 3.3%. Conclusions The inpatient burden of PAD is considerable in Slovenia. Patients hospitalised for PAD have a high burden of comorbidities, especially when presenting with chronic limb-threatening ischaemia; nonetheless, in-hospital major amputations and mortality decreased substantially over the last decade.